Does Advertising Affect Gender Perception? - Usman, Mohammed; ., . (International Journal of Engineering and Technology, 2019)
Gender representations in advertising can easily reflect â€œfundamental features of the social structure,â€ such as values, beliefs, or norms. Research has mainly proceeded on the lines of content analysis, which refers to the study of representation of characters in the advertisements from the viewpoint of relative role played by men and women. This paper explores the attitudes of the viewers numbering 451 from Bangalore Urban District towards television advertising. The results indicate that (i) Women perceive benefits of television advertising at higher levels than men. (ii) Women perceive abuse of women in television advertising at higher levels than men.Â Â